Standards applied by the school nurse versus the knowledge and attitudes of secondary school students concerning normal body weight - Szadowska-Szlachetka, Zdzisława; Stanisławek, Andrzej; Charzyńska-Gul, Marianna; Kachaniuk, Hanna; Muzyczka, Katarzyna (Polish Journal of Public Health, 2009)
Introduction. Standards of the prophylactic healthcare of students are aimed at achieving the uniformity of procedures applied by the school nurse. In the Polish population, adolescents using slimming diets are found increasingly frequently. In spite of that fact, the percentage of overweight people is constantly increasing. Therefore, it is important for adolescents to gain an objective and full knowledge on proper nutrition as well as on methods and criteria of assessing body weight.Objective. The paper aimed at presenting the tasks of the school nurse in the field of prophylactic healthcare standards as well as to obtain information about the level of knowledge of students concerning the rules of a healthy diet, together with benefits resulting from obeying these rules and risks associated with ignoring them.Material and methods. The empirical material was collected with the use of the diagnostic survey method. The applied tool was a questionnaire. The survey included 42 students of one of the secondary schools in Lublin. Results. On the basis of the BMI calculation, it was determined that 23% is underweight, 71% has normal body weight, and 4% of students are overweight. Overweight is claimed by 23% of people with objectively normal body weight while those who are underweight (23%) claim that their body weight is normal.Conclusions. The level of general knowledge about rules of proper nutrition can be assessed as suffi cient. However, a discrepancy between the objective knowledge on the method and criteria of determining normal body weight in the case of the surveyed and their subjective self-assessment, i.e. their belief that they are overweight, may be regarded as alarming. It is recommended that parents, teachers and educators pay attention to the proper nutrition of adolescents.